The Influence of Social Media on Consumptive Behavior Economic Education Students in Purchasing Products MSMEs - Ramadhani, Nabila Rizki; Rinaldi, Muammar; Dianita, Ami; Safitri, Laila; Hasibuan, Muhammad Rifqi Farhan; Azzahra, Nabila; Lubis, Nazia Safira (Outline Journal of Management and Accounting, 2025)
This study aims to examine the influence of social media on student consumer behavior in purchasing MSME products. Using a quantitative survey-based method, data were collected through an online questionnaire involving 30 Economic Education students as respondents. The results of the analysis show that social media significantly influences student consumer behavior, contributing 35.2% to the variability of their consumption behavior. Social media, such as Instagram, TikTok, and Facebook, are used by MSME actors to market products through visual content, reviews, and endorsements that attract students' attention. This study recommends increasing digital and financial literacy for students, as well as more educational marketing strategies from MSME actors.